Clinical course and progression-free survival of adult intracranial and spinal ependymoma patients. Issue 3 (13th August 2014) - Vera-Bolanos, Elizabeth; Aldape, Kenneth; Yuan, Ying; Wu, Jimin; Wani, Khalida; Necesito-Reyes, Mary Jo; Colman, Howard; Dhall, Girish; Lieberman, Frank S.; Metellus, Philippe; Mikkelsen, Tom; Omuro, Antonio; et al.
Abstract: Background: Ependymomas are rare CNS tumors. Previous studies describing the clinical course of ependymoma patients were restricted to small sample sizes, often with patients at a specific institution. Methods: Clinically annotated ependymoma tissue samples from 19 institutions were centrally reviewed. Patients were all adults aged 18 years or older at the time of diagnosis. Potential prognostic clinical factors identified on univariate analysis were included in a multivariate Cox proportional hazards model with backwards selection to model progression-free survival. Results: The 282 adult ependymoma patients were equally male and female with a mean age of 43 years (range, 18–80y) at diagnosis. The majority were grade II (78%) with the tumor grade for 20 cases being reclassified on central review (half to higher grade). Tumor locations were spine (46%), infratentorial (35%), and supratentorial (19%). Tumor recurrence occurred in 26% ( n = 74) of patients with a median time to progression of 14 years. A multivariate Cox proportional hazards model identified supratentorial location ( P < .01), grade III (anaplastic; P < .01), and subtotal resection, followed or not by radiation ( P < .01), as significantly increasing risk of early progression. Conclusions: We report findings from an ongoing, multicenter collaboration from a collection of clinically annotated adult ependymoma tumor samples demonstrating distinct predictors of progression-free survival. This unique resource provides the opportunity to better define the clinical course of ependymoma for clinical and translational studies.